Educação ambiental no licenciamento: um estudo do programa de educação ambiental na transamazônica - município de Brasil Novo-Pará - MAFRA, Kelly Soares (Universidade Federal do Pará, 2015)
This paper presents a study on the environmental education program of the BR-230 held in the Brazilian city New Brazil, state of Para, during the environmental licensing process of the work of paving of BR-230 (Trans) highway. The objective refers to an analysis of the results of actions taken by the Environmental Education Program of BR-230 in the municipality of Novo Brazil, from 2009 to 2011 The theoretical and methodological framework of a qualitative approach that focuses on the analysis the Environmental Education Program from the perspective of critical environmental education. The collection and analysis of data was carried out semi-structured interviews directed to basic education teachers and supplemented with information sought documents related to the Program. The results of the survey scale the importance of theoretical reflection on pedagogical processes used to carry out the Environmental Education Program under the. The research reveals from the analysis of the statements of interviewees that there is a joint effort between the proposed action developed by the Program and environmental issues of local reality; the actions provided subject to new knowledge and experiences that are meaningful in their teaching practices, as in the preparation of projects and the improvement of educational planning. Therefore the environmental actions taken by the BR-230 program are relevant and contribute to a critical reflection on the lifestyle and culture of the individuals involved, however, it is seen in the testimonies the need to overcome the conservationist vision as a possible expansion of prospect of action.